Application of the New Public Relations Paradigm in the Cyberspace Retail Industry - Setiawan, Deddy (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2024)
This research aims to analyze the application of the New Public Relations (NPR) paradigm in the retail industry, by taking a case study of a well-known retail company, Alfamart. The NPR paradigm emphasizes the importance of two-way interaction between organizations and stakeholders, as well as an emphasis on values, transparency, and community involvement. This study uses a qualitative approach with data collection techniques in the form of in-depth interviews with various related parties in Alfamart, such as senior management, PR staff, and consumers. Data analysis was conducted by detailing communication practices that reflect the NPR paradigm. The results of this study reveal that Alfamart has implemented various aspects of the NPR paradigm in its communication strategy. They understand the importance of listening to input and feedback from consumers and strive to provide honest, transparent and relevant information to stakeholders. In addition, Alfamart is also active in involving themselves in social and community activities, reflecting their commitment to corporate social responsibility. This research contributes to the understanding of how retail companies can adopt the NPR paradigm in managing relationships with consumers and society more effectively. This research contributes to the understanding of how retail companies can adopt the NPR paradigm in managing relationships with consumers and society more effectively.